Dorsal Midbrain Syndrome: Clinical and Imaging Features in 75 Cases. Issue 4 (December 2021) - Yousif, Jonah E.; Liao, Eric; Trobe, Jonathan D.
Abstract : Background: Dorsal midbrain syndrome (DMS) consists of a constellation of clinical features, including reduced upgaze, pupillary light-near dissociation, lid retraction, convergence retraction, and eye misalignment. This syndrome results mostly from intrinsic or extrinsic mesodiencephalic tumors or strokes, obstructive hydrocephalus, failure of cerebrospinal fluid shunting to correct obstructive hydrocephalus, and head trauma. Published reports that include imaging corroboration are based on relatively small cohorts and have not included comprehensive patient self-reports on the impact of these abnormalities on quality of life. Methods: We conducted a retrospective review of cases of DMS identified between 1998 and 2019 at the University of Michigan using the Electronic Medical Record Search Engine. Patients were included only if they had been evaluated by a neuro-ophthalmologist and had a corroborative imaging abnormality. We collected data on symptoms and on neuro-ophthalmic and neurologic signs. We reviewed brain imaging reports on all 75 patients, and the study neuroradiologist analyzed the imaging in 57 patients. Using a uniform list of questions, we conducted telephone interviews of 26 patients to assess lingering symptoms and their impact on quality of life. Results: There were 75 patients, only 5 of whom were younger than 10 years. Neoplasms accounted for 47%, strokes (mostly thalamic) for 25%, nonneoplastic masses for 12%, nonneoplastic hydrocephalus for 7%, traumatic brain injury for 5%, and demyelination for 4%. Reduced upgaze occurred in 93% of patients, being completely absent or reduced to less than 50% amplitude in 67%. Convergence retraction on attempted upgaze occurred in 52%, horizontal misalignment in 49%, vertical misalignment in 47%, and pupillary light-near dissociation in 37%. Optic neuropathy attributed to chronic papilledema occurred in only 3%. Three or more neuro-ophthalmic signs were present in 84%, and only 4% had a single sign—reduced upgaze. Imaging features did not correlate with the frequency or severity of clinical signs. There was some improvement in the clinical signs among the patients with stroke but no change among the patients with neoplasms. In the 26 telephone interviews, patients with neoplasms reported that imbalance had a greater impact on quality of life than did diplopia. Patients with strokes reported that imbalance had the greatest impact initially but that its effect dissipated. Neither group reported lingering effects of impaired upgaze. Conclusions: This large series expands on the clinical profile of DMS. Neoplasms and strokes were the most common causes. Obstructive hydrocephalus alone, identified as a major cause in the largest previously published series, was uncommon. At least 3 neuro-ophthalmic signs were present in nearly all patients, with upgaze deficit as predominant. Unlike an earlier report, this study found no correlation between brain imaging and clinical signs. Neuro-ophthalmic signs persisted even after neoplasms were successfully treated and improved only slightly after stroke. Telephone interviews with patients revealed that diplopia and upgaze deficit had less lasting impact on quality of life than did ataxia and concurrent nonneurologic problems. Abstract : Supplemental Digital Content is Available in the Text.